2015
DOI: 10.35188/unu-wider/2015/952-7
|View full text |Cite
|
Sign up to set email alerts
|

Needs vs expediency: Poverty reduction and social development in post-conflict countries

Abstract: Conflict depletes all forms of human and social capital, as well as supporting institutions. The scale of the human damage can overwhelm public action, as there are many competing priorities and resources are often insufficient. What then should be the priorities for 'post-conflict' policy? Should it give, for example, higher priority to health or to livelihoods in allocating the resources available (financial, human, and institutional)? Should social protection be the main focus of effort and, if so, what for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…A more general policy implication could be to prioritize provision of healthcare in postconflict societies, not only to adults but also to children (Addison et al, 2016). While there are policies in place to assist war veterans with mental health problems such as posttraumatic stress disorder (PTSD), children who grow up during the war without participating are often overlooked from a policy perspective.…”
Section: Resultsmentioning
confidence: 99%
“…A more general policy implication could be to prioritize provision of healthcare in postconflict societies, not only to adults but also to children (Addison et al, 2016). While there are policies in place to assist war veterans with mental health problems such as posttraumatic stress disorder (PTSD), children who grow up during the war without participating are often overlooked from a policy perspective.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have found that political instability significantly reduces economic growth, as measured by the annual rate of change in gross domestic product (Abadie and Gardeazabal 2003;Alesina et al 1996;Lai and Thyne 2007;Shields and Paulson 2015). Addison et al (2015) found further that political violence threatens both human and social capital and weakens institutions. While examining changes in global education spending and enrollment over an 18year period (1980-1997), Lai and Thyne (2007) found that political instability reduces the amount of resources put into education and undermines a state's ability to perform its basic functions, such as providing services.…”
Section: Human Capital and Political Violencementioning
confidence: 99%
“…The resultant humanitarian situation was considered catastrophic, with millions of people displaced and nearly half the new nation's population facing a severe food shortage (IPC 2017). The destruction of physical capital in recent years thwarted the fundamental development process in South Sudan, with basic services gravely affected (Mayai and Hammond 2014;Addison et al 2015;Lai and Thyne 2007;Burde et al 2017). This included institutions in the education sector, which struggled to perform their duties as learning facilities, became homes for armed groups, were destroyed, or closed down.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation